Anti-dazzle hard coating liquid, preparation method of anti-dazzle hard coating liquid, anti-dazzle hard coating film and image display device
By using a multifunctional main resin, a multifunctional diluted monomer and a modified porous silica, the problem of insufficient hardness and wear resistance of the existing anti-glare hardening film is solved, and an anti-glare hardening film with high hardness, wear resistance and good anti-glare effect is achieved.
Patent Information
- Application Number
- CN202411915057.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing anti-glare hardness has low surface hardness and poor wear resistance, and is prone to damage due to contact, friction, scratches, etc. with other hard objects.
An anti-glare hard coating liquid is made of multifunctional host resin, multifunctional diluted monomer and modified porous silica. A high-hardness shell layer is formed on the surface of the porous silica through a double-curing resin, and it participates in the photocuring reaction of the hardened film layer to enhance the crosslinking degree and binding force.
The anti-glare hardened film has good wear resistance, surface hardness and anti-glare performance, and improves the protection effect of the display while achieving good anti-glare effect.
Smart Images

Figure CN119708989A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hardened films, and in particular to an anti-glare hard coating liquid and a preparation method thereof, as well as an anti-glare hardened film and an image display device. Background Art
[0002] The surface of the anti-glare hardened film has a concave-convex structure, which can effectively reduce the light reflected by the screen. Therefore, attaching the anti-glare hardened film to the surface of the display screen can effectively solve the visibility problem in a strong light environment. However, the surface hardness of the existing anti-glare hardened film is low and the wear resistance is poor, which makes the surface of the display screen easily damaged by contact with other hard objects, friction, scratches, etc. Summary of the invention
[0003] In order to solve the above-mentioned technical problems, the purpose of this application includes providing an anti-glare hard coating liquid and its preparation method, as well as an anti-glare hardened film and an image display device. The anti-glare hardened film made from the anti-glare hard coating liquid can have good wear resistance, surface hardness and anti-glare performance, and can improve the protection effect of the display screen while achieving good anti-glare effect.
[0004] In a first aspect, the present application provides an anti-glare hard coating liquid, comprising a multifunctional main resin, a multifunctional diluent monomer and modified porous silica; wherein the modified porous silica comprises porous silica and a shell layer coated on the surface of the porous silica, and the shell layer is formed by curing a dual-curing resin.
[0005] In the above technical scheme, the anti-glare hard coating liquid provided by the present application is added with modified porous silica. Since porous silica has a large specific surface area, the dual-cured resin is cured on its surface to form a high-hardness shell layer with a strong bond, and the dual-cured resin can also participate in the subsequent photocuring cross-linking reaction of the hardened film layer, thereby enhancing the degree of cross-linking with the main resin and improving the bonding force between the modified porous silica and the hardened film layer, so that the anti-glare hardened film prepared by the anti-glare hard coating liquid can have good wear resistance, surface hardness and anti-glare performance. In addition, by using a multifunctional main resin and combining a multifunctional diluent monomer, the degree of cross-linking of the hardened film layer can be effectively increased, thereby further enhancing the surface hardness and wear resistance of the anti-glare hardened film.
[0006] In some embodiments, the cured dual-cured resin is also filled in the pores of the porous silica. The dual-cured resin is not only cured and coated on the surface of the porous silica, but also filled in the pores of the porous silica, thereby further improving the hardness of the modified porous silica and further improving the surface hardness and wear resistance of the anti-glare hardened film.
[0007] In some embodiments, the dual-curing resin includes at least one of a hydroxyl-containing acrylic resin or an isocyanate-containing acrylic resin. These dual-curing resins all have dual-curing properties, can be thermally cured with a curing agent on the surface of porous silica to form a high-hardness shell layer, and can further participate in the photocuring reaction of the hardened film layer to increase the crosslinking density.
[0008] In some embodiments, the average particle size of the porous silica is 2-8 μm. By controlling the average particle size of the porous silica, the modified porous silica can be effectively filled in the hardened film layer to achieve an anti-glare effect, while improving the coating modification effect of the dual-curing resin.
[0009] In some embodiments, the multifunctional main resin includes one of polyurethane acrylate oligomers, silicone acrylate oligomers, or polyester acrylate oligomers with a functionality of 6 to 9; the multifunctional diluent monomer includes an acrylate monomer with a functionality of 3 to 6. By controlling the functionality and type of the multifunctional main resin and the multifunctional diluent monomer, the crosslinking density can be further increased, thereby improving the wear resistance of the anti-glare hardened film.
[0010] In some embodiments, the anti-glare hard coating liquid includes the following components by weight: 15-40 parts of a multifunctional main resin, 4-15 parts of a multifunctional diluent monomer, 1-4 parts of a photoinitiator, 0.8-5 parts of modified porous silica, 20-200 parts of a first solvent, and 0.01-0.3 parts of a leveling agent.
[0011] In the above technical scheme, by controlling the appropriate ratio of each component, the comprehensive performance of the anti-glare hardened film can be optimized. At a relatively small thickness, it has appropriate haze and good anti-glare performance, as well as higher hardness and excellent wear resistance.
[0012] In the second aspect, the present application provides a method for preparing the above-mentioned anti-glare hard coating liquid, comprising the following steps: mixing a dual-cure resin, a thermal curing agent, a second solvent and a dispersant to obtain a dual-cure modified liquid; adding porous silica to the dual-cure modified liquid, heating and curing after mixing to obtain modified porous silica; mixing a multifunctional main resin, a multifunctional diluent monomer, a photoinitiator, modified porous silica, a first solvent and a leveling agent to obtain an anti-glare hard coating liquid.
[0013] In the above technical scheme, since porous silica has a large specific surface area, a high-hardness shell layer can be formed on the surface of porous silica by mixing a dual-cured resin with porous silica and then performing thermal curing. At the same time, part of the dual-cured resin will also fill into the pores of porous silica, and the hardness of the modified porous silica can be further improved after curing. By adding modified porous silica to the anti-glare hard coating liquid, its surface has a high-hardness shell layer, and the shell layer can further participate in the ultraviolet light curing reaction of the hardened film layer, thereby improving the degree of cross-linking with the main resin, so that the anti-glare hardened film can have good wear resistance, surface hardness and anti-glare performance. In addition, by adopting a multifunctional main resin and using a multifunctional diluent monomer, the curing and cross-linking effect can be improved, thereby improving the surface hardness and wear resistance of the anti-glare hardened film. The preparation method prepares modified porous silica by thermal curing, and then mixes the raw materials evenly to obtain an anti-glare hard coating liquid. The entire preparation process is simple, the process conditions are controllable, and it is easy to achieve large-scale application.
[0014] In some embodiments, the mass ratio of the dual-cure resin to the porous silica is (20-40):(2-4). By controlling the amount of the dual-cure resin, the dual-cure resin can be fully coated on the surface of the porous silica after curing.
[0015] In some embodiments, the dual-cure modified liquid includes, by weight: 20-40 parts of dual-cure resin, 20-200 parts of second solvent, 0.02-2 parts of dispersant and 0.02-5 parts of thermal curing agent; the conditions for heat curing include: heat curing at 80-120°C for 1-5 minutes; after heat curing, it also includes: grinding.
[0016] In the above technical solution, by controlling the raw material dosage of the dual-curing modified liquid and the heat curing reaction conditions, the uniform protective shell layer formed on the porous silica surface can be effectively controlled. The uniformity of the protective shell layer coating on the porous silica surface and the uniformity of the particle size can be further controlled by grinding.
[0017] In a third aspect, the present application provides an anti-glare hardened film, including a base film and a hardened film layer attached to the surface of the base film, wherein the hardened film layer is obtained by coating and photocuring the above-mentioned anti-glare hard coating liquid.
[0018] In the above technical solution, the anti-glare hardened film prepared by the above anti-glare hard coating liquid has good wear resistance, surface hardness and anti-glare performance, which improves the protection effect of the display screen while achieving good anti-glare effect.
[0019] In a fourth aspect, the present application provides an image display device, comprising the anti-glare hardened film. Since the anti-glare hardened film has excellent anti-glare performance, high wear resistance and high surface hardness, it has a good protective effect on the surface of the image display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 A process flow chart of a method for preparing an anti-glare hard coating liquid provided in an embodiment of the present application. DETAILED DESCRIPTION
[0022] In a strong light environment, the display screen will reflect a large amount of external light, which reduces the contrast of the displayed image and affects the visual effect. By attaching an anti-glare film to the surface of the display screen, due to the concave-convex structure on its surface, the light reflected by the screen can be effectively reduced, reducing eye fatigue. However, the current anti-glare film has a low hardness and poor wear resistance, and the surface of the display screen is easily scratched when in contact with hard objects and friction. Existing studies have disclosed the use of multifunctional acrylic resins and high-hardness silica particles in the hardened film layer to improve the wear resistance, but due to the weak physical interaction between the multifunctional acrylic resin and the silica particles, the effect of improving the wear resistance is limited.
[0023] Based on this, the present application provides an anti-glare hard coating liquid, which adopts a multifunctional main resin and a multifunctional dilution monomer, and combines with the addition of modified silica. The surface of the modified silica has a high hardness shell layer formed by curing the dual-cure resin, and the dual-cure resin can further participate in the photocuring reaction of the hardened film layer, thereby increasing the degree of cross-linking with the hardened film layer and enhancing the bonding force between the modified silica and the hardened film layer, thereby effectively improving the hardness and wear resistance of the anti-glare hardened film.
[0024] The following is a detailed description of the anti-glare hard coating liquid and its preparation method, as well as the anti-glare hardened film and the image display device of the embodiment of the present application:
[0025] Figure 1 This is a process flow chart of a method for preparing an anti-glare hard coating liquid provided in an embodiment of the present application. Figure 1 , the preparation method comprises the following steps:
[0026] S110, mixing a dual-cure resin, a thermal curing agent, a second solvent and a dispersant to obtain a dual-cure modified liquid; adding porous silica to the dual-cure modified liquid, mixing and heating and curing to obtain modified porous silica.
[0027] The dual-curing resin undergoes a thermal curing reaction under the action of a thermal curing agent, is coated on the porous silica to form a high-hardness shell layer, and is partially filled in the pores of the porous silica.
[0028] In some embodiments, the dual-cure modified liquid includes, by weight: 20-40 parts of dual-cure resin, 20-200 parts of second solvent, 0.02-2 parts of dispersant, and 0.02-5 parts of thermal curing agent.
[0029] As an example, by weight, the amount of dual-cure resin added to the dual-cure modifying liquid is 20 parts, 30 parts or 40 parts; the amount of the second solvent added is 50 parts, 80 parts or 100 parts; the amount of the dispersant added is 0.8 parts, 1.2 parts or 1.6 parts; the amount of the thermal curing agent added is 2.5 parts, 3.75 parts or 5 parts; the amount of porous silica added is 2 parts or 4 parts.
[0030] It should be noted that the "dual-curing resin" referred to in this application refers to a resin that has another curing mode in addition to light curing, for example, a resin that has both light curing and heat curing properties.
[0031] In some embodiments, the dual-curing resin may be at least one of a hydroxyl-containing acrylic resin or an isocyanate-containing acrylic resin. By way of example, the hydroxyl-containing acrylic resin may be a hydroxyl-containing polyurethane acrylate or a hydroxyl-containing polyester acrylate. In the hydroxyl-containing acrylic resin, the hydroxyl portion may undergo a thermal curing reaction together with a thermal curing agent, while the acrylate portion may undergo a photocuring reaction.
[0032] In some embodiments, the thermal curing agent can be an aliphatic isocyanate or an aromatic isocyanate; the dispersant can be a phenolic, alkyd, or polyurethane; the second solvent can be ethyl acetate, butyl acetate, toluene, xylene, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol ethyl ether, ethylene glycol butyl ether, propylene glycol butyl ether, butylene glycol butyl ether, dipropylene glycol methyl ether, or a mixture thereof.
[0033] The porous silica in the present application is spherical silica with a porous structure on the surface, which can be a commercially available product or prepared by conventional methods in the art. As an example, the porous silica used in the embodiments of the present application can be prepared by the following method: mixing isopropanol and spherical silica, adjusting the pH value to 9-11, stirring and performing solid-liquid separation; adding the treated spherical silica to a sodium hydroxide solution for etching, and then performing solid-liquid separation, washing, and drying to obtain porous silica.
[0034] In some embodiments, the porous silica has an average particle size of 2-8 μm and a specific surface area of 50-400 m 2As an example, the average particle size of the porous silica is 3 μm, 6 μm, or 8 μm.
[0035] The mass ratio of the dual-cured resin to the porous silica is (20-40):(2-4). As an example, the mass ratio of the dual-cured resin to the porous silica is 20:2, 30:4, or 40:2.
[0036] In some embodiments, after adding porous silica to the dual-cure modified liquid, the mixture may be mixed evenly at a stirring speed of 500-2000 rpm.
[0037] In some embodiments, the heat curing conditions include: heat curing at 80-120° C. for 1-5 min. For example, heat curing at 120° C. for 2 min or heat curing at 80° C. for 5 min.
[0038] In some embodiments, the method further comprises grinding and sieving after heating and curing, for example, grinding repeatedly and then filtering 3-5 times with a 3-8 μm sieve to obtain modified porous silica.
[0039] S120, mixing a multifunctional main resin, a multifunctional diluent monomer, a photoinitiator, modified porous silica, a first solvent and a leveling agent to obtain an anti-glare hard coating liquid.
[0040] In some embodiments, the anti-glare hard coating liquid includes, by weight: 15-40 parts of a multifunctional main resin, 4-15 parts of a multifunctional diluent monomer, 1-4 parts of a photoinitiator, 0.8-5 parts of modified porous silica, 20-200 parts of a first solvent, and 0.01-0.3 parts of a leveling agent.
[0041] Preferably, the anti-glare hard coating liquid comprises, by weight, 20-40 parts of a multifunctional main resin, 5-15 parts of a multifunctional diluent monomer, 1.5-3.5 parts of a photoinitiator, 1-2.5 parts of modified porous silica, 40-100 parts of a first solvent, and 0.02-0.25 parts of a leveling agent.
[0042] As an example, in parts by weight, the amount of the multifunctional main resin added to the anti-glare hard coating liquid is 15 parts, 20 parts, 25 parts or 30 parts; the amount of the multifunctional diluent monomer added is 5 parts, 6 parts, 8 parts or 10 parts; the amount of the photoinitiator added is 1 part, 1.6 parts, 2 parts or 2.5 parts; the amount of the modified porous silica added is 1.1 parts, 1.5 parts, 2 parts or 2.5 parts; the amount of the first solvent added is 50 parts, 80 parts or 100 parts; the amount of the leveling agent added is 0.02 parts, 0.05 parts or 0.1 parts.
[0043] It can be understood that the "multifunctionality" mentioned in the present application refers to a compound having three or more active functional groups.
[0044] Among them, the multifunctional main resin as the main resin of the photocuring reaction contains three or more active functional groups, which can effectively improve the crosslinking degree of the photocuring reaction. In some embodiments, the multifunctional main resin can be one of a polyurethane acrylate oligomer, a silicone acrylate oligomer or a polyester acrylate oligomer with a functionality of 6 to 9.
[0045] The multifunctional diluent monomer refers to a monomer containing three or more active functional groups and having a diluting effect in the photocuring system, which can be used to reduce the viscosity of the photocuring system and participate in the photocuring reaction. In some embodiments, the multifunctional diluent monomer can be an acrylate monomer with a functionality of 3 to 6, such as one or more of pentaerythritol hexaacrylate, pentaerythritol triacrylate, and trihydroxymethylpropane triacrylate.
[0046] The photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone (184), 2-hydroxy-2-methyl phenyl propiophenone (1173) or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO). The leveling agent is fluorinated acrylic or silicone.
[0047] The first solvent can be ethyl acetate, butyl acetate, propylene glycol monomethyl ether acetate, toluene, xylene, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol ethyl ether, ethylene glycol butyl ether, propylene glycol butyl ether, butylene glycol butyl ether, dipropylene glycol methyl ether or a mixture thereof.
[0048] In the present application, the porous silica is modified by coating the surface with a dual-curing resin. On the one hand, the dual-curing resin forms a high-hardness shell layer on the surface of the porous silica by acting with a thermal curing agent. Since the porous silica has a large specific surface area, it is easier to coat, and the shell layer is firmly bonded to the particles themselves. Part of the dual-curing resin can also be filled in the pores on the surface of the porous silica, thereby enhancing the hardness of the modified silica. On the other hand, the photocurable part of the dual-curing resin, such as the acrylate part of the hydroxyl-containing acrylic resin, can subsequently participate in the photocuring reaction with the main resin, thereby increasing the crosslinking degree of the hardened film layer and the bonding force between the modified silica and the hardened film layer, thereby further improving the surface hardness and wear resistance of the anti-glare hardened film.
[0049] The embodiment of the present application also provides an anti-glare hardened film, including a base film and a hardened film layer attached to the surface of the base film, and the hardened film layer is obtained by coating and photocuring the above-mentioned anti-glare hard coating liquid.
[0050] In some embodiments, the thickness of the hardened film layer is 3-10 μm, and the thickness of the base film is 20-200 μm.
[0051] In some embodiments, the material of the base film includes but is not limited to polyethylene terephthalate (PET), triacetyl cellulose (TAC), polypropylene (PP), polyethylene (PE), polyimide (PI) or polymethyl methacrylate (PMMA).
[0052] The method for preparing the anti-glare hardened film may include: coating the anti-glare hard coating liquid on the surface of the base film, and performing ultraviolet light curing after drying to form a hardened film layer to obtain the anti-glare hardened film.
[0053] The method of coating the anti-glare hard coating liquid can be slit coating, micro gravure coating, blade coating, Mayer rod coating, roller coating and blade coating to form a coating layer. If the coating method is selected as micro gravure coating and slit coating, the coating effect can be better.
[0054] After the anti-glare hard coating liquid is applied, the anti-glare hard coating liquid is dried in an environment of 60 to 80° C. for 2 to 4 minutes. For example, the anti-glare hard coating liquid is dried at a temperature of 60° C., 70° C., or 80° C.; and the hard coating liquid is dried for 2 minutes, 2.2 minutes, 2.5 minutes, 2.8 minutes, or 3 minutes.
[0055] The energy of UV curing is 200mJ / cm 2 -600mJ / cm 2 As an example, the energy of UV curing is 200 mJ / cm 2 、300mJ / cm 2 or 500mJ / cm 2 wait.
[0056] In addition, the embodiment of the present application also provides an image display device using the anti-glare hardened film. The image display device includes but is not limited to a mobile phone display screen, a liquid crystal display LCD, a light-emitting diode display ELD, etc.
[0057] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0058] The sources of some raw materials in the following examples and comparative examples are shown in Table 1:
[0059] Table 1 Source of raw materials
[0060]
[0061] The modified porous silica in the following examples is prepared by the following method:
[0062] (1) Preparation of porous silica: isopropanol and spherical silica were mixed in a mass ratio of 2.5:1, the pH value was adjusted to 9 with ammonia water, stirred at 50°C for 3 hours, centrifuged and dried at 60°C; the spherical silica treated as above was added to a 0.1 mol / L sodium hydroxide solution for etching for 0.5 hours, then centrifuged, washed with water, and dried at 60°C to obtain porous silica.
[0063] (2) Preparing modified porous silica: Mixing a hydroxyl-containing acrylate, a thermal curing agent, a dispersant and a second solvent by weight to obtain a dual-cure modified liquid; adding the above-mentioned porous silica to the dual-cure modified liquid, stirring and mixing at 800 rpm, thermally curing at 100° C. for 2 min, repeatedly grinding, and filtering 3 to 5 times using a 3-8 μm mesh to obtain the modified porous silica.
[0064] The difference between the preparation methods of modified silica and modified porous silica is that step (1) is not included. The components of modified silica and modified porous silica are shown in Table 2:
[0065] Table 2 Components of modified porous silica and modified silica (parts by weight)
[0066]
[0067] Example
[0068] The present embodiment provides an anti-glare hardened film, comprising a TAC base film (with a thickness of 80 μm) and a hardened film layer (with a thickness of 7 μm) attached to the surface of the TAC base film, and a preparation method thereof comprises the following steps:
[0069] (1) mixing a multifunctional main resin, a multifunctional diluent monomer, a photoinitiator, modified porous silica, a first solvent and a leveling agent to obtain an anti-glare hard coating liquid;
[0070] (2) The anti-glare hard coating liquid was applied to the surface of the TAC base film, dried at 80°C for 2 min, and then heated with 300 mJ / cm 2 UV energy is used for UV curing to form a hardened film layer, thereby obtaining an anti-glare hardened film.
[0071] The preparation methods of the anti-glare hardened films in Examples 1 to 4 and Comparative Examples 1 to 6 are substantially the same, the only difference being the amount of each component in the anti-glare hard coating solution and the type of modified porous silica, as shown in Table 2 for details.
[0072] Table 2 Amount of each component in the anti-glare hard coating solution of the embodiment and the comparative example (parts by weight)
[0073]
[0074]
[0075] Test example
[0076] The anti-glare hardened films prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were subjected to performance tests, and the test methods were as follows:
[0077] 1. Haze
[0078] The haze of the antiglare cured film was measured by a transmitted light method using a Nippon Denshoku NDH 2000N haze meter in accordance with JIS K-7105.
[0079] 2. Wear-resistant
[0080] Use #0000 steel wool with a weight of 1000g to rub back and forth on the hardened coating surface 1000 times to observe whether the coating is scratched. Press the steel wool #0000, 2cm×2cm wear-resistant head to the coating surface of the film with a weight of 1000g, and then observe the damage state of the film surface and make a judgment. Use a three-wavelength daytime white fluorescent lamp (NationalPalook, F.L15EX-N 15W) as the light source, and observe the reflected light from the upper side with the naked eye to make a judgment. If there is no scratch, it is recorded as O; if there is a broken scratch and slight particle wear, it is recorded as X; if there is a long scratch accompanied by moderate to severe particle wear, it is recorded as N.
[0081] 3. Hardness
[0082] Refer to JIS K-5600-5-4 specification, use 3M-P1000 sandpaper to grind the tip of Mitsubishi H pencils of different numbers, and then fix the pencils on the hand-push pencil hardness tester. Select five areas in the full width direction of the film, add 500g weights, and measure them separately. Use your hand to push the pencil hardness tester horizontally, with a moving speed of 1mm / s, and move a distance of 30-50mm. After gently wiping the surface with an eraser, use a fluorescent lamp to visually check in all directions to see if there are any scratches. If there are no scratches, it means it has passed (the first 3mm is not counted). The larger the number before H, the higher the hardness.
[0083] 4. Anti-glare performance
[0084] The anti-glare hardened film is attached to a black acrylic plate, and the degree of reflection of the observer's background is observed and evaluated. If the observer cannot be clearly seen, the anti-glare effect is good and is recorded as OK; if the observer's background can be clearly seen, the anti-glare effect is poor and is recorded as NG.
[0085] The above performance test results are shown in Table 3.
[0086] Table 3 Performance test results of anti-glare hardened films in Examples and Comparative Examples
[0087] Group Haze(%) Wear-resistant hardness Anti-glare effect Example 1 13.81 O 4H OK Example 2 19.24 O 4H OK Example 3 30.29 O 4H OK Example 4 8.03 O 4H OK Comparative Example 1 11.65 X 3H OK Comparative Example 2 21.33 X 3H OK Comparative Example 3 14.01 N 3H OK Comparative Example 4 15.42 N 2H OK Comparative Example 5 23.97 N 2H OK Comparative Example 6 13.25 N 2H OK
[0088] It can be seen from Table 2 and Table 3 that the anti-glare hardened films prepared in Examples 1 to 4 of the present application all have good anti-glare effect, excellent wear resistance and high hardness, and have suitable haze. By introducing modified porous silica into the anti-glare hardened film, the hardness of the anti-glare hardened film can reach 4H, and there is no obvious scratch after wiping 1000 times under a load of 1000g (excellent wear resistance), and there is no obvious effect on the haze and anti-glare effect.
[0089] By comparing the performance test results of Examples 1 to 2 and Comparative Examples 1 to 2, it can be seen that the wear resistance and hardness are significantly reduced when modified silica is used instead of modified porous silica. This may be because porous silica has a larger specific surface area, and the resin is filled into the pores on the surface of the porous silica and coated on the surface of the porous silica to form a shell layer, so that the bonding force between the surface coating shell layer and the porous silica is higher, and the modification effect is better.
[0090] By comparing the performance test results of Example 1 and Comparative Example 3, it can be seen that the use of thermally curable acrylic resin instead of dual-curing resin can only thermally cure to participate in the formation of a coating shell layer on the surface of the porous silica, but cannot subsequently participate in the photocuring cross-linking reaction of the hardened film layer, resulting in a reduced degree of cross-linking, reduced bonding between the modified porous silica and the hardened film layer, and significantly reduced wear resistance and hardness.
[0091] Comparing the performance test results of Example 1 with those of Comparative Examples 4 and 6, and comparing the performance test results of Example 2 with those of Comparative Example 5, it can be seen that without modifying the spherical silica or porous silica, the surface hardness and wear resistance of the anti-glare hardened film are significantly reduced.
[0092] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. An anti-glare hard coating liquid, characterized in that: It comprises a multifunctional main resin, a multifunctional diluent monomer and modified porous silica; wherein the modified porous silica comprises porous silica and a shell layer coated on the surface of the porous silica, and the shell layer is formed by curing a dual-curing resin.
2. The anti-glare hard coating liquid according to claim 1, characterized in that: The cured dual-cured resin also fills the pores of the porous silica.
3. The anti-glare hard coating liquid according to claim 1, characterized in that: The dual-cure resin includes at least one of a hydroxyl-containing acrylic resin or an isocyanate-containing acrylic resin; And / or, the average particle size of the porous silica is 2-8 μm.
4. The anti-glare hard coating liquid according to claim 1, characterized in that: The multifunctional main resin includes one of a polyurethane acrylate oligomer, a silicone acrylate oligomer or a polyester acrylate oligomer with a functionality of 6 to 9; And / or, the multifunctional diluent monomer includes an acrylic ester monomer with a functionality of 3 to 6.
5. The anti-glare hard coating liquid according to claim 1, characterized in that: The anti-glare hard coating liquid comprises, by weight: 15-40 parts of a multifunctional main resin, 4-15 parts of a multifunctional diluent monomer, 1-4 parts of a photoinitiator, 0.8-5 parts of modified porous silica, 20-200 parts of a first solvent, and 0.01-0.3 parts of a leveling agent.
6. A method for preparing the anti-glare hard coating liquid according to any one of claims 1 to 5, characterized in that: The following steps are involved: The dual-cure resin, the thermal curing agent, the second solvent and the dispersant are mixed to obtain a dual-cure modified liquid; porous silica is added to the dual-cure modified liquid, mixed and heated to obtain modified porous silica; The multifunctional main resin, the multifunctional diluent monomer, the photoinitiator, the modified porous silica, the first solvent and the leveling agent are mixed to obtain the anti-glare hard coating liquid.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the dual-cured resin to the porous silica is (20-40):(2-4).
8. The preparation method according to claim 6, characterized in that: The dual-cure modified liquid comprises, by weight: 20-40 parts of dual-cure resin, 20-200 parts of a second solvent, 0.02-2 parts of a dispersant, and 0.02-5 parts of a thermal curing agent; And / or, the conditions for heat curing include: heat curing at 80-120° C. for 1-5 min; And / or, after the heating and curing, the method further comprises: grinding.
9. An anti-glare hardened film, characterized in that: The invention comprises a base film and a hardened film layer attached to the surface of the base film, wherein the hardened film layer is obtained by coating and light curing the anti-glare hard coating liquid according to any one of claims 1 to 5.
10. An image display device, characterized in that: The anti-glare hardening film according to claim 9 is included.